Race, science, and medicine, 1700-1960 - Harris, Bernard, 1961-; Ernst, Waltraud, 1955- (London ; New York : Routledge, 1999)
Race, Science and Medicine, 1700-1960 brings together current critical research into the role played by racial ideas in the production of medical knowledge, throwing new light on three centuries of racial and medical history.
Introduction: historical and contemporary perspectives on race, science and medicine / Waltraud Ernst -- Western medicine and racial constitutions: surgeon John Atkins' theory of polygenism and sleepy distemper in the 1730s / Norris Saakwa-Mante -- From the land of the Bible to the Caucasus and beyond: the shifting ideas of the geographical origin of humankind / H.F. Augstein -- Colonial policies, racial politics and the development of psychiatric institutions in early nineteenth-century British India / Waltraud Ernst -- Racial categories and psychiatry in Africa: the asylum on Robben Island in the nineteenth century / Harriet Deacon -- 'An ancient race outworn': malaria and race in colonial India, 1860-1930 / David Arnold -- Tuberculosis and race in Britain and its empire, 1900-50 / Michael Worboys -- Changing depictions of disease: race, representation and the history of 'mongolism' / Mark Jackson -- Pro-alienism, anti-alienism and the medical profession in late-Victorian and Edwardian Britain / Bernard Harris -- A virulent strain: German bacteriology as scientific racism, 1890-1920 / Paul Weindling -- 'Savage civilization': race, culture and mind in Britain, 1898-1939 / Mathew Thomson -- 'New men, strange faces, other minds': Arthur Keith, race and the Piltdown affair (1912-53) / Jonathan Sawday.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Social medicine -- History; Colonization -- Health aspects -- History; Imperialism -- Health aspects -- History; Science -- Social aspects -- History; Medicine -- History; Social Medicine -- history; Social Sciences -- history; Racial Groups -- history; History of Medicine; Médecine sociale -- Histoire; Colonisation -- Aspect sanitaire -- Histoire; Impérialisme -- Aspect sanitaire -- Histoire; Sciences -- Aspect social -- Histoire; Médecine -- Histoire; history of medicine; MEDICAL -- History; Colonization -- Health aspects; Imperialism -- Health aspects; Science -- Social aspects; Social medicine; Geneeskunde; Rassendiscriminatie; Kolonialisme; Wetenschap; History